Canadian Association of Radiologists Guidance on Contrast-Associated Acute Kidney Injury. (May 2022) - Macdonald, D. Blair; Hurrell, Casey D.; Costa, Andreu F.; McInnes, Matthew D. F.; O'Malley, Martin; Barrett, Brendan J.; Brown, Pierre Antoine; Clark, Edward G.; Hadjivassiliou, Anastasia; Kirkpatrick, Iain Donald Craik; Rempel, Jeremy; Jeon, Paul; et al.
Purpose: Iodinated contrast media is one of the most frequently administered pharmaceuticals. In Canada, over 5.4 million computed tomography (CT) examinations were performed in 2019, of which 50% were contrast enhanced. Acute kidney injury (AKI) occurring after iodinated contrast administration was historically considered a common iatrogenic complication which was managed by screening patients, prophylactic strategies, and follow-up evaluation of renal function. The Canadian Association of Radiologists (CAR) initially published guidelines on the prevention of contrast induced nephropathy in 2007, with an update in 2012. However, new developments in the field have led to the availability of safer contrast agents and changes in clinical practice, prompting a complete revision of the earlier recommendations. Information sources: Published literature, including clinical trials, retrospective cohort series, review articles, and case reports, along with expert opinions from radiologists and nephrologists across Canada. Methods: The leadership of the CAR formed a working group of radiologists and nephrologists with expertise in contrast administration and patient management related to contrast-associated AKI. We conducted a comprehensive review of the published literature to evaluate the evidence about contrast as a cause of AKI, and to inform evidence-based recommendations. Based on the available literature, the working group developed consensus recommendations. Key Findings: The working group developed 21 recommendations, on screening, choice of iodinated contrast media, prophylaxis, medication considerations, and post contrast administration management. The key changes from the 2012 guidelines were (1) Simplification of screening to a simple questionnaire, and not delaying emergent examinations due to a need for creatinine measurements (2) Prophylaxis considerations only for patients with estimated glomerular filtration rate (eGFR) less than 30 mL/min/1.73 m2 (3) Not recommending the routine discontinuation of any drugs to decrease risk of AKI, except metformin when eGFR is less than 30 mL/min/1.73 m2 and (4) Not requiring routine follow up serum creatinine measurements post iodinated contrast administration. Limitations: We did not conduct a formal systematic review or meta-analysis. We did not evaluate our specific suggestions in the clinical environment. Implications: Given the importance of iodinated contrast media use in diagnosis and management, and the low risk of AKI after contrast use, these guidelines aim to streamline the processes around iodinated contrast use in most clinical settings. As newer evidence arises that may change or add to the recommendations provided, the working group will revise these guidelines.